2015
DOI: 10.1155/2015/612642
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Negative Effects of Elevated Intra‐Abdominal Pressure on Pulmonary Mechanics and Oxidative Stress

Abstract: Objective. To compare the effects of pneumoperitoneum on lung mechanics, end-tidal CO2 (ETCO2), arterial blood gases (ABG), and oxidative stress markers in blood and bronchoalveolar lavage fluid (BALF) during laparoscopic cholecystectomy (LC) by using lung-protective ventilation strategy. Materials and Methods. Forty-six patients undergoing LC and abdominal wall hernia (AWH) surgery were assigned into 2 groups. Measurements and blood samples were obtained before, during pneumoperitoneum, and at the end of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Findings of these studies supporting correlations of changes in arterial blood gases with the end-tidal CO 2 concentration, as well as ventilation parameters and dynamic lung compliance [ 1 3 ], were in accordance with results by Strang et al [ 9 ] concerning arterial pCO 2 to end-tidal CO 2 gradient, which is strongly correlated with the amount of atelectasis estimated by an end-expiratory transversal spiral computed tomography with subsequent calculation of the total lung volume with further analysis of the lung tissue density as normally, poorly, over-, and nonaerated (atelectasis) regions.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…Findings of these studies supporting correlations of changes in arterial blood gases with the end-tidal CO 2 concentration, as well as ventilation parameters and dynamic lung compliance [ 1 3 ], were in accordance with results by Strang et al [ 9 ] concerning arterial pCO 2 to end-tidal CO 2 gradient, which is strongly correlated with the amount of atelectasis estimated by an end-expiratory transversal spiral computed tomography with subsequent calculation of the total lung volume with further analysis of the lung tissue density as normally, poorly, over-, and nonaerated (atelectasis) regions.…”
mentioning
confidence: 71%
“…We read with great interest the recently published article by Davarcı et al [ 1 ] in your journal aimed at studying the effects of CO 2 -pneumoperitoneum at 12 mm Hg intraperitoneal pressure on end-tidal CO 2 (P ET CO 2 ) concentration, arterial blood gas values and oxidative stress markers in blood, and bronchial lavage during laparoscopic cholecystectomy using a long protective strategy since our clinical [ 2 ] and experimental [ 3 ] results were in line with findings of this study [ 1 ]. The authors clearly demonstrated significant changes of the peak in respiratory pressure, dynamic lung compliance, P ET CO 2 , arterial pO 2 , pCO 2 , and pH values at the 30th min of CO 2 -pneumoperitoneum in comparison with parameters of both at the baseline and at the end of surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid carbon dioxide intoxication, we normally did not raise the pneumoperitoneum pressure. We believe that will burden a relative risk of cardiopulmonary function on patients, which could also influence the postoperative recovery [5,6]. Finally, a running vesicourethral anastomosis is achieved by using a 2 X T4 taper, 14 cm × 14 cm, double-armed barbed suture (Quill™ SRS, Angiotech, Reading, PA) and the Van Velthoven technique [7].…”
Section: Ligation-free Techniquementioning
confidence: 99%